Preinjury to Postinjury Disablement and Recovery After a Lateral Ankle Sprain: A Case Report - Fraser, John J. (J Athl Train, 2018)
A healthy 19-year-old male college student (height = 177.8 cm, mass = 64.3 kg, body mass index = 20.3 kg/m(2), Foot Posture Index = −1) participating in a study sustained a grade 2 inversion lateral ankle sprain 3 days after completing patient-reported outcome measures. A treatment protocol including therapeutic exercises and midfoot mobilizations was provided. Patient-reported outcomes assessing physical health, mental health, and foot-ankle function were completed 3 days preinjury and 1, 3, and 12 weeks postinjury. Substantial postinjury changes in function, physical health, and kinesiophobia reflected functional limitations that improved with treatment and time. This level 3 exploration case report provides a rare opportunity to highlight preinjury-to-postinjury changes in patient-reported physical and psychological measures caused by a lateral ankle sprain.